EVALUATION OF NON-ADHERENCE TO ANTITUBERCULAR DRUGS AMONG TUBERCULOSIS PATIENTS: A PROSPECTIVE STUDY - LATA, SUMAN; KHAJURIA, VIJAY; SAWHNEY, VINEETA; KUMARI, KAMLESH (International Journal of Current Pharmaceutical Research, 2021)
Objective: The objective of present study was to examine the non-adherence among tuberculosis patients to antitubercular drugs and the factors associated with non-adherence. Methods: Prospective observational study was conducted in department of pharmacology Government Medical College, Kathua in collaboration with the district tuberculosis centre, Kathua for a period of four months. TB Patients on treatment for last 8 w were included in the study. The pre validated questionnaire was provided to patients and their responses were analysed. Morisky’s Medication Adherence Scale (MMAS-4) was used to assess adherence/non-adherence to antitubercular drugs. Results: Total 72 patients were included in trial and out of which 60(83.33%) were males and12 (16.66%) were females and the maximum were between 40-50y (38%) of age, mostly illiterate (50%) and from lower socioeconomic status (38%). Out of 60 male patients, 48(80%) showed adherence to anti-tuberculosis drugs, while remaining 12(20%) were non-adherent. Whereas 10females (83%) were adherent and 2 (16.66%) were non-adherent. Forgetfulness (42%), followed by illiteracy (21.4%) and longer distance from health institute (14%) were main reasons for non-adherence. Conclusion: Present study has shown non-adherence is maximum among males, illiterate, low socioeconomic group, longer distance from the health institution.